Structural Optimization of Vertical Axis Wind Turbine (VAWT): A Multi-Variable Study for Enhanced Deflection and Fatigue Performance - Sajid Ali; Hongbae Park; Daeyong Lee (Journal of Marine Science and Engineering)
This study covers the structural optimization of vertical axis wind turbines (VAWTs) that can operate reliably for long periods of time in marine environments, as well as simulation analysis to evaluate their fatigue and strain resistance. Due to the nature of the marine environment, strong wind speeds and constant wave loads are applied, and VAWTs are likely to suffer from fatigue build-up and deformation problems in the long term. In this study, detailed numerical simulations were performed using ANSYS software (2024 R2) to analyze the effects of different airfoil shapes, material choices, tip speed ratios (TSRs), and foundation types on the turbine’s stress distribution and fatigue resistance. The results showed that NACA 0030 airfoil, composite steel, and single-pile foundation performed best under TSR 1.8 conditions, with the potential to reduce strain by approximately 30% and fatigue damage by approximately 25% compared to conventional structures. With this optimized combination, it was found that maintenance costs could be significantly reduced while maintaining structural stability at sea. These results could make an important contribution to the economical and durable design of VAWTs in the future.